Organo‐Acid Catalysed Synthesis of 2, 2‐Disubstituted Chromans and 1, 1‐Disubstituted Indanols/ Indenols. Issue 24 (24th June 2021) - Behera, Sagarika; Bera, Nabakumar; Sarkar, Debayan
Abstract: An organo‐acid catalyzed approach towards the synthesis of 1, 1‐dialkyl‐2, 3‐dihydro‐indenols and 2, 2‐disubstituted chromans have been achieved. Indane and chroman analogous provide a significant understanding of the chemistry of biological systems. The present reaction condition and the yield achieved is the best amongst the available organo‐catalytic strategies Abstract : This report entails an interesting trifluoroacetic acid‐catalyzed synthesis of 1, 1‐dialkyl‐2, 3‐dihydro‐indenols and 2, 2‐disubstituted chromans. The present reaction condition and the yield achieved is the best amongst the available organo‐catalytic strategies with minimum reaction time from easily available starting materials. The interesting 7‐membered benz‐oxapin has been achieved by this protocol which was not reported earlier. This report will provide a versatile pathway towards the synthesis of various chroman‐based natural products.